A new index to measure cost of living for expatriates in cities. Issue 3 (21st May 2018) - Tan, Khee Giap; Luu, Nguyen Trieu Duong; Nguyen, Le Phuong Anh
Abstract : Purpose: Cost of living is an important consideration for the decision-making of expatriates and investment decisions of businesses. As competition between cities for talent and capital becomes global instead of national, the need for timely and internationally comparable information on global cities' cost of living increases. While commercial research houses frequently publish cost of living surveys, these reports can be lacking in terms of scientific rigour. In this context, this paper aims to contribute to the literature by formulating a comprehensive and rigorous methodology to compare the cost of living for expatriates in 103 world's major cities. Design/methodology/approach: A cost of living index for expatriates composed of the ten consumption categories is constructed. The results from the study covers a study period from 2005 to 2014 in 103 cities. More than 280 individual prices of 165 goods and services have been compiled for each city in the calculation of the cost of living index for expatriates. New York has been chosen as the base city for the study, with other cities being benchmarked against it. A larger cost of living index for expatriates implies that the city is more expensive for expatriates to live in and vice versa. Findings: While the authors generate the cost of living rankings for expatriates for 103 cities worldwide, in this paper, the authors focus on five key cities, namely, London, Hong Kong, Singapore, Tokyo and Zurich, as they are global financial centres. In 2013, the latest year for which data are available, Zurich was the most expensive for expatriates among the five cities, followed by Singapore, Tokyo, London and Hong Kong. These results pertain to the cost of living for expatriates, and cities compare very differently in terms of cost of living for ordinary residents, as ordinary residents follow different consumption patterns from expatriates. Originality/value: Cost of living in the destination city is a major consideration for professionals who look to relocate, and organisations factor such calculations in their decisions to post employees overseas and design commensurate compensation packages. This paper develops a comprehensive and rigorous methodology for measuring and comparing cost of living for expatriates around the world. The value-addition lies in the fact that the authors are able to differentiate between expatriates and ordinary residents, which has not been done in the existing literature. They use higher quality data and generate an index that is not sensitive to the choice of base city.